An Inhibitory Motif on the 5'UTR of Several Rotavirus Genome Segments Affects Protein Expression and Reverse Genetics Strategies. - Giuditta De Lorenzo; Marija Drikic; Guido Papa; Catherine Eichwald; Oscar R Burrone; Francesca Arnoldi (PLoS ONE, 2016)
Rotavirus genome consists of eleven segments of dsRNA, each encoding one single protein. Viral mRNAs contain an open reading frame (ORF) flanked by relatively short untranslated regions (UTRs), whose role in the viral cycle remains elusive. Here we investigated the role of 5'UTRs in T7 polymerase-driven cDNAs expression in uninfected cells. The 5'UTRs of eight genome segments (gs3, gs5-6, gs7-11) of the simian SA11 strain showed a strong inhibitory effect on the expression of viral proteins. Decreased protein expression was due to both compromised transcription and translation and was independent of the ORF and the 3'UTR sequences. Analysis of several mutants of the 21-nucleotide long 5'UTR of gs 11 defined an inhibitory motif (IM) represented by its primary sequence rather than its secondary structure. IM was mapped to the 5' terminal 6-nucleotide long pyrimidine-rich tract 5'-GGY(U/A)UY-3'. The 5' terminal position within the mRNA was shown to be essentially required, as inhibitory activity was lost when IM was moved to an internal position. We identified two mutations (insertion of a G upstream the 5'UTR and the U to A mutation of the fifth nucleotide of IM) that render IM non-functional and increase the transcription and translation rate to levels that could considerably improve the efficiency of virus helper-free reverse genetics strategies.